2003
DOI: 10.1007/s00592-003-0021-2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting bone mineral density of postmenopausal healthy and cirrhotic Italian women using age and body mass index

Abstract: The objective of the present report was to develop mathematical prediction formulae for the lumbar spine, pelvis and total bone mineral density (BMD) based on the osteoporosis risk factors age and BMI in healthy and cirrhotic postmenopausal women. The study population comprised 20 postmenopausal cirrhotic women (late PM cirrhotic women), 20 postmenopausal healthy women matched for age and BMI (late PM healthy women), and 19 younger postmenopausal healthy women matched for BMI (early PM healthy women). Segmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“… 51 BMI was found to be significantly correlated with aBMD. 52 Putman et al 53 also found the differences in radius cortical thickness and tibia bone size between patient with cystic fibrosis and controls were from BMI. In this study, to eliminate the BMI effect and examine the underlying bone microstructural and mechanical differences between Hispanic and Caucasian women, we incorporated BMI as covariant in the general linear model.…”
Section: Discussionmentioning
confidence: 95%
“… 51 BMI was found to be significantly correlated with aBMD. 52 Putman et al 53 also found the differences in radius cortical thickness and tibia bone size between patient with cystic fibrosis and controls were from BMI. In this study, to eliminate the BMI effect and examine the underlying bone microstructural and mechanical differences between Hispanic and Caucasian women, we incorporated BMI as covariant in the general linear model.…”
Section: Discussionmentioning
confidence: 95%
“…Several risk factors are implicated in favoring postmenopausal bone loss. Important nonmodifiable predictors of bone demineralization are age, sex, period of amenorrhea [31, 32], and parental history of fracture [33]. Important modifiable factors are dietary calcium intake [34, 35], low body mass index [31, 36, 37], smoking [3840], reduced physical activity [41, 42], and high alcohol intake [43].…”
Section: Postmenopausal Osteoporosismentioning
confidence: 99%
“…There is a well established relationship between bone mineral density (BMD) and the ability of bone to withstand trauma, such that 60-70% of the variance in bone strength depends on BMD [4][5][6]. Fracture risk increases 1.5-3 fold for each standard deviation (SD) fall in BMD [4]; osteoporosis was defined on the basis of bone mineral density (BMD) assessment by the WHO in 1994 [7], so the assessment of this parameter is still a crucial point for the diagnosis of osteoporosis, nevertheless there are poor data in literature about osteoporosis prevalence as diagnosed by bone densitometry [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Several risk factors, both modifiable or not, are implied in favouring postmenopausal bone loss. Among non-modifiable factors important predictors of bone demineralization are: age, sex, period of amenorrhea [8,9] and parental history of fracture [10]. Important modifiable factors are: dietary calcium intake [11][12][13][14][15][16], low body mass index [8,17,18], smoking [19][20][21], reduced physical activity [22,23], and high alcohol intake [24,25], nevertheless their role in determining who should have BMD measurement is yet poorly validated.…”
Section: Introductionmentioning
confidence: 99%